La narrazione necessaria: Il metodo biografico come percorso catartico - Gasparetti, Simona (B@belonline, 2021)
The essay highlights the narrative traces in the path to the Self that each individual man and all humanity in its history has followed. Verbal traces, but also traces expressed in images. Following the traces opens up a glimpse into the other side of the world. Listening to a story is a way of arousing amazement and of re-enchantment in the listener. The essay then sets out a particular case of the use of autobiography in the Medical Humanities.